Acoustic therapy for allergic rhinitis and chronic rhinosinusitis: modulating microbiome, immunity and well-being - Alao, Jude Oluwapelumi; Lau, Kelvin E. M.; White, David; Lee, Kevin; Puli'uvea, Chris; Bartley, Jim (Frontiers in Allergy, 2025)
Allergic rhinitis (AR) and chronic rhinosinusitis (CRS) are common respiratory conditions that significantly impact patient health and contribute to substantial healthcare burdens. While conventional treatments offer symptom relief, many patients continue to experience persistent symptoms, side effects, or resistance to standard therapies. This highlights the growing need for novel, non-invasive, and sustainable therapeutic strategies to manage chronic airway inflammation. This review examines acoustic therapy, an emerging non-pharmacological treatment that uses sound wave-induced vibrations as a potential adjunctive therapy for AR and CRS. Acoustic therapy shows potential benefits, including enhanced nitric oxide production, improved mucociliary clearance, and modulation of immune responses by activating mechanosensitive pathways and disrupting pathogenic biofilms. Preliminary clinical findings across some trials have reported improvements in peak nasal inspiratory flow ranging from approximately 17% to 31%, significant reductions in nasal congestion and symptom scores, such as Total Nasal Symptom Score, Sino-Nasal Outcome Test-22 (SNOT-22), and enhancements in sleep quality and patient-reported outcomes. Given this limited but expanding body of evidence, we integrate interdisciplinary insights from respiratory medicine, immunology, and microbiome science to provide a translational framework for future research. We highlight the need for rigorously designed clinical trials to assess acoustic therapy's therapeutic efficacy, safety, and long-term impact. As this field evolves, acoustic therapy holds significant potential to address unmet needs in chronic respiratory diseases and contributes to improved patient care.